2019
DOI: 10.1080/13669877.2018.1503614
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of the concept of ‘uncertain risk’. A qualitative study among different societal groups

Abstract: View related articles View Crossmark data Citing articles: 2 View citing articles Understanding of the concept of 'uncertain risk'. A qualitative study among different societal groups

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Newspaper articles sometimes seemed to refer to the probability of health effects using the term “risk.” The word risk, however, can vary in intended and perceived meaning; it could for example refer to the presence of a hazardous substance, the possibility of a health effect or the probability of a health effect. Furthermore, Jansen, Claassen, van Kamp, and Timmermans ( 2019 ) found that laypersons associate “risk” often with danger (Jansen et al., 2019 ). The observed lack in essential contextual information and in explanations of the technical terms used is in congruence with the results from previous studies on media coverage of risks (Freimuth et al., 1984 ; Wahlberg & Sjoberg, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Newspaper articles sometimes seemed to refer to the probability of health effects using the term “risk.” The word risk, however, can vary in intended and perceived meaning; it could for example refer to the presence of a hazardous substance, the possibility of a health effect or the probability of a health effect. Furthermore, Jansen, Claassen, van Kamp, and Timmermans ( 2019 ) found that laypersons associate “risk” often with danger (Jansen et al., 2019 ). The observed lack in essential contextual information and in explanations of the technical terms used is in congruence with the results from previous studies on media coverage of risks (Freimuth et al., 1984 ; Wahlberg & Sjoberg, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, participants often believed that scientists have determined that a substance is a health hazard, while in fact this was not the case (c.f. Jansen et al, 2019). Misinterpretations like these are likely to affect perceptions of food safety (Verbeke et al, 2007) and trust in authorities (Campbell, 2011; Poortinga and Pidgeon, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wiedemann et al (2014) showed that the public greatly overestimated the magnitude of risk when interpreting “possibly carcinogenic,” while in fact the technical risk (chance × effect) is still undetermined. Also, Jansen et al (2019) showed that members of the general public often associate the term “uncertain risk” with a lack of personal control, low likelihood, and uncertainties due to delayed effects, all implying that the public assumes that a risk exists. People may have negative associations with specific words.…”
Section: Introductionmentioning
confidence: 99%